PERANAN NILAI TERHADAP PERILAKU KEWARGANEGARAAN ORGANISASI: STUDI PILOT PADA KARYAWAN DI DEPOK, INDONESIA - Novika Grasiaswaty (Universitas Bunda Mulia, 2018)
Organization Citizenship Behavior (OCB) is known to have important role for supporting employee performance in a company. Considering this positive outcomes for company, many researcher began to gave interest on this topic. This study aimed to see the role of personal value on employees OCB behavior. The study was conducted on 30-dyads employee and their supervisor from several types of industrial backgrounds. Unlike previous OCB studies in Indonesia, this time, OCB would be measured using a rating from the supervisor. Personal value will be masured by employee self-report. Thus, common method variance bias can be avoided. The result show that only achievement values significantly affect OCB behavior, meanwhile power and benevolence did not significantly affect OCB behavior. Keyword: Organization Citizenship Behavior, Indonesian employee, Personal Value